Toward synthesis of thioglycosyl-phosphonate analogues of lipid ll - Kelemen, Viktor; Csiszár, Milán; Borbás, Anikó (De Remediis, 2024)
Although a multitude of epidemics have already been eradicated with the use of modern antibiotics, in the 20th century, a new and increasingly serious phenomenon has arisen - the resistance against antibiotic therapies, necessiting the need for the development of novel antibiotic compounds. Transglycosylases are key enzymes in the biosynthesis of the bacterial cell wall, and currently there is no approved drug in human use against them, so they are an excellent target for further antibiotic development. During our research, the main goal was to synthesize compounds that are structurally similar to lipid ll, the substrate of bacterial transglycosylases, however, with significant modifications, such as the incorporation of an α-thioglycosidic unit instead of the α-O-glycosidic bond and an alkylphosphonate unit instead of the pyrophosphate part, making the molecules suitable to act as enzyme inhibitors. The key step of our work is the stereoselective construction of the 1,2-cis-α-thioglycosidic bond by photoinitiated thiol ene coupling reaction. ln this paper, the novel synthesis route is described which can be applied to furnish different lipid ll analogues, on example synthesis of a D-glucose derivative.